2012
DOI: 10.1155/2012/327269
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Packet Entropy for Heart Murmurs Classification

Abstract: Heart murmurs are the first signs of cardiac valve disorders. Several studies have been conducted in recent years to automatically differentiate normal heart sounds, from heart sounds with murmurs using various types of audio features. Entropy was successfully used as a feature to distinguish different heart sounds. In this paper, new entropy was introduced to analyze heart sounds and the feasibility of using this entropy in classification of five types of heart sounds and murmurs was shown. The entropy was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Due to the denoising of the signal the results achieved were better. Wavelet based PCG signal analysis achieved accuracy of 90% -97.56% [7,13,14,16]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the denoising of the signal the results achieved were better. Wavelet based PCG signal analysis achieved accuracy of 90% -97.56% [7,13,14,16]. …”
Section: Resultsmentioning
confidence: 99%
“…The best results were achieved using Bayes Net as a classifier with an accuracy of 96.94%. The results showed that the proposed wavelet packet entropy was effective for heart sounds classification [14]. In 2013, Sun et al combined Improved EMD (Empirical Mode Decomposition) and Shannon energy envelope algorithm for extraction of S1 and S2 components and achieved a high accuracy of 99.74% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some variations of WPE have been proposed by several researchers. In [6], entropy was calculated using crest energy in each subband of WPD results. Meanwhile, Shannon method was used in WPD subband for bearing inspection in [16].…”
Section: Related Workmentioning
confidence: 99%
“…It uses Shannon entropy calculations on the subband of discrete wavelet transform (DWT) [5]. The improvement of the wavelet entropy is the wavelet packet entropy (WPE) that uses the wavelet packet decomposition (WPD) subband [6]. WE produced low accuracy when used as a feature for pulmonary sound classification as reported in [7].…”
Section: Introductionmentioning
confidence: 99%
“…PCG signal processing is one of the active research areas [1]- [3]. A considerable body of these researches is dedicated to heart sound classification.…”
Section: Introductionmentioning
confidence: 99%